Analisis Yuridis Tentang Perlindungan Hukum Terhadap Tenaga Kerja Honorer Berdasarkan Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Khusnul Ikhsana; Kosariza Kosariza (Universitas Jambi, Fakultas Hukum, 2022)
The purpose of this study is to 1) To analyze the legal arrangements for honorary workers based on Law Number 5 of 2014 concerning State Civil Apparatus. 2) To analyze the legal protection of honorary workers based on Law Number 5 of 2014 concerning State Civil Apparatus . The formulation of the research problems are: 1) What are the legal arrangements for honorary workers based on Law Number 5 of 2014 concerning State Civil Apparatus? 2) How is the legal protection for honorary workers based on Law Number 5 of 2014 concerning State Civil Apparatus? Honorary and State Civil Apparatus. The approach used is the statutory approach, conceptual approach and case approach. The technique of collecting legal materials is by conducting a systematization and then doing a qualitative descriptive analysis and drawing conclusions in a deductive way. Based on the results of the study, it can be concluded that, after the enactment of Law Number 5 of 2014 the arrangement of Honorary Personnel remains as Honorary Personnel. Not all Honorary Personnel can be appointed as CPNS based on Government Regulation Number 48 of 2005. However, Honorary Personnel who were appointed under 2005 have the opportunity to be appointed as CPNS according to the provisions stipulated in PP Number 48 of 2005 as amended several times recently. with Government Regulation Number 56 of 2012, while for Honorary Personnel whose appointments were above 2005 have the opportunity to be appointed as PPPK and/or CPNS after the provisions that regulate further on this matter.